Leaky Scanning Is the Predominant Mechanism for Translation of Human Papillomavirus Type 16 E7 Oncoprotein from E6/E7 Bicistronic mRNA - Stacey, Simon N. (American Society for Microbiology, 2000)
Human papillomaviruses (HPV) are unique in that they generate mRNAs that apparently can express multiple proteins from tandemly arranged open reading frames. The mechanisms by which this is achieved are uncertain and are at odds with the basic predictions of the scanning model for translation initiation. We investigated the unorthodox mechanism by which the E6 and E7 oncoproteins from human papillomavirus type 16 (HPV-16) can be translated from a single, bicistronic mRNA. The short E6 5′ untranslated region (UTR) was shown to promote translation as efficiently as a UTR from Xenopus β-globin. Insertion of a secondary structural element into the UTR inhibited both E6 and E7 expression, suggesting that E7 expression depends on ribosomal scanning from the 5′ end of the mRNA. E7 translation was found to be cap dependent, but E6 was more dependent on capping and eIF4F activity than E7. Insertion of secondary structural elements at various points in the region upstream of E7 profoundly inhibited translation, indicating that scanning was probably continuous. Insertion of the E6 region between Renilla and firefly luciferase genes revealed little or no internal ribosomal entry site activity. However when E6 was located at the 5′ end of the mRNA, it permitted over 100-fold-higher levels of downstream cistron translation than did the Renilla open reading frame. Internal AUGs in the E6 region with strong or intermediate Kozak sequence contexts were unable to inhibit E7 translation, but initiation at the E7 AUG was efficient and accurate. These data support a model in which E7 translation is facilitated by an extreme degree of leaky scanning, requiring the negotiation of 13 upstream AUGs. Ribosomal initiation complexes which fail to initiate at the E6 start codon can scan through to the E7 AUG without initiating translation, but competence to initiate is achieved once the E7 AUG is reached. These findings suggest that the E6 region of HPV-16 comprises features that sponsor both translation of the E6 protein and enhancement of translation at a downstream site.